PEROLEHAN SILIKAT DARI ABU SEKAM PADI DALAM SPOUTED-BED: EFEK PERPINDAHAN MASSA - Sitompul, Johnner P; Wanadri, Agus (Mesin, 1996)
A 5 cm diameter spouted-bed reactor has been applied for solid-liquid reaction, paddy ash and NaOH producing Na-silicate. Hydrodinamics of spouted-bed reactor was studied by using paddy ash-water system. Correlation for minimum superfisial spouting (Ums) was determined and follows the equation.Â ( in cgs unit)The spouted bed (SB) operates under transition regime i.e. Reynold number particle range 7-25 or Re number ï¬uid ranging from 19 to 254. The mass transfer is the controlling step for this system as for all solid-liquid reactions are very fast. So, a model of mass transfer has been derived and mass transfer correlation in SB follows equations Sh = 191,34 + 0,6325 Sc0.35 Re1.89 Above correlation shows high mass transfer at stagnant ï¬uid compared to other mass transfer correlations which is due to reacting system involved.Kata kunci : sunbungan adhesives, perfonnansi kekakuan. performansi perpindahan panas.